Starotestamentalny ideał: śmierć w „dobrym wieku”, we właściwym czasie i okolicznościach - Janusz Lemański (Studia Paradyskie)
The description of the “ideal” end of human life found in the Penateuch is the fruit of theological thought of priestly authors (cf. Gen 25,7-11). It contains the idea od “satiety” (a sense of fulfillment in life: e.g. economic success, offspring), information about death at the “right time” (cf. Ps 90,10) and generation change (burial by sons and transition to the circle of ancestors). In the case of patriarchs, above average life expectancy (cf. Gen 6,3) has a symbolic dimension (a special expression of God’s blessing). The priestly formula of description has in part its source in Deuteronomistic information about the death of subsequent rulers (to rest with one’s father/s), which expressed only legal succession to the throne (cf. 1Kings 2,10) after the death of the predecessor. Later authors (Chronicles, Job) extended this ideal to other characters (David, Jojada, Job).